Digital Marketing, Relationship, and Customer Trust As Key of Brand Loyalty: A Case Study of Skintific in Tangerang - Ramadhani, Nurdyanti; Prastowo, Sugeng Lubar; Isrial, Isrial (IJBLE Scientific Publications Community Inc., 2025)
This study examines the influence of digital marketing, relationship, and customer trust on Skintific brand loyalty in Tangerang City, amid intense competition in the beauty industry. Using a quantitative associative approach, data were collected from 223 Skintific customers selected through accidental sampling. A structured questionnaire was administered, and the data were analysed using SmartPLS 3.2.9, with tests including validity, reliability, model fit, R², and path coefficients. The results show that digital marketing positively and significantly increases brand loyalty by 36.7%, relationship contributes positively and significantly by 10.2%, and customer trust exerts the strongest positive and significant effect, increasing loyalty by 38.8%. These findings highlight the critical role of integrated digital engagement, sustained customer relationships, and trust-building in fostering brand loyalty in competitive markets.